1989
DOI: 10.1177/00220345890680111401
|View full text |Cite
|
Sign up to set email alerts
|

Stiffness of Endodontically-treated Teeth Related to Restoration Technique

Abstract: Endodontically-treated posterior teeth are susceptible to fracture; consequently, full-occlusal-coverage restorations are recommended. We designed this study to examine the potential for alternative restorative techniques for pulpless teeth, using strain gauges mounted on extracted maxillary second premolars to measure strains generated by nondestructive occlusal loading. Cuspal stiffness was evaluated on the following sequentially performed procedures: unaltered tooth, completion of all endodontic procedures,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
140
1
5

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(149 citation statements)
references
References 19 publications
3
140
1
5
Order By: Relevance
“…In Case of Paradigm MZ the results could be transferable to Lava TM Ultimate (3M Espe, Seefeld, Germany) due to the similar mechanical properties like Youngs modulus. Ceramic restorations provide a higher modulus of elasticity that reduces deformation of the tooth and therefore deformations at the margin of the restoration [73].…”
Section: Discussionmentioning
confidence: 99%
“…In Case of Paradigm MZ the results could be transferable to Lava TM Ultimate (3M Espe, Seefeld, Germany) due to the similar mechanical properties like Youngs modulus. Ceramic restorations provide a higher modulus of elasticity that reduces deformation of the tooth and therefore deformations at the margin of the restoration [73].…”
Section: Discussionmentioning
confidence: 99%
“…The important role of loss of the marginal ridges in reducing fracture resistance in endodontically treated teeth was also reported in other studies. 3,7,[32][33][34] In the current study, cuspal reinforcement using bonded composite restoration can partially compensate for the compromised fracture resistance. 18,21 However, adhesive restoration alone is not capable of restoring fracture resistance to the level seen in intact posterior teeth.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Numerous studies have reported a high incidence of fracture in endodontically treated maxillary premolars. 2,5,6 Susceptibility to fracture is the result of the loss of marginal ridges and the pulp chamber roof during access preparation 2,7,8 and is a concern, particularly in maxillary premolars, because their anatomy facilitates separation of the cusps during mastication. 9 Fractures in the unsupported tooth structure can lead to restorative difficulties and even extraction if the tooth is unrestorable.…”
Section: Introductionmentioning
confidence: 99%
“…Overall stress distribution within the tooth/restoration complex is determined by geometry and hard tissue/restorative material arrangement. 27 As demonstrated by Reeh et al, 28 non-destructive approaches, rather than experimental load-to-failure, may be the best approach to determining significant differences in stress distribution. Non-destructive approaches can provide greater insight into the performance of both tooth and restorative materials but may require complex modeling tools such as the finite element (FE) method.…”
mentioning
confidence: 99%